Study of the entrepreneurial profile of production engineering students from a Federal University in Brazil - Gambi, Lillian Do Nascimento; Menezes, Evandro Galvão Tavares (Revista Gestão da Produção Operações e Sistemas, 2020)
With the increasing importance of entrepreneurship for the economic and social development of the country, it is essential that higher education institutions are aware of their role in the training of its students. Therefore, the purpose of this study is to identify the entrepreneur profile of Production Engineering students in a Higher Education Institution located in Southeast region in Brazil, to compare the data with the results provided in the report “Entrepreneurship in Brazilian Universities” developed by Endeavor Brazil and Sebrae, and to contribute to developing strategies to foster entrepreneurship in the institution and in the region where the HEI is located. Therefore, it was performed a case study encompassing 43 students in the eighth semester of the Production Engineering course. The results show that it is necessary to improve the activities related to entrepreneurship, providing theoretical background and practical activities as well to stimulate students’ creativity and willingness to become entrepreneurs. The results also show a lack of innovative mindset in the undergraduate students, reinforcing the need of developing initiatives that foster the students to thinking in an innovative way as the development of policies to approach HEIs and the private sector allowing the development of creative solutions better aligned to the market’s demands. This study only covered students from the eighth semester of the Production Engineering Course and from one single HEI, so the results cannot be generalized. Future research should use different methods such as survey research to extend the sample beyond the HEI studied, and longitudinal case studies to develop a better understanding of the findings described in this study.